Pengaruh Product Quality dan Brand Trust terhadap Repurchase Intention Melalui Customer Satisfaction sebagai Variabel Intervening pada Produk Kecantikan Brand Somethinc - Yunita Aprilia; Sonja Andarini (Research and Strategic Studies Center (Pusat Riset dan Kajian Strategis) Fakultas Syariah IAI Nasional Laa Roiba, 2023)
The purpose of this study was to analyze the effect of product quality and brand trust on repurchase intention through customer satisfaction as an intervening variable in Something beauty products. This study used a quantitative method by distributing questionnaires online to 100 respondents. The population in this study involves consumers who have repeatedly purchased products from Something in 2022. Based on data analysis techniques using validity tests, reliability tests, classical assumption tests, statistical tests and hypothesis tests using path analysis and Sobel test analysis with the help of data processing programs using SPSS for windows version 25. The results of this study are 1) Product Quality has a positive and insignificant effect on repurchase intention of Something products 2) Brand Trust has a negative and insignificant effect on repurchase intention of Something products. 3) Product Quality has a positive and significant impact on customer satisfaction of Something's product. 4) Brand Trust has a positive and significant influence on customer satisfaction of Something products. 5) Customer satisfaction has a positive and significant effect on repurchase intention of Something's product. 6) Product Quality has a positive and significant influence on repurchase intention through Customer Satisfaction of Something product. 7) Brand Trust has a negative and insignificant effect on repurchase intention through Customer Satisfaction of Something products. Keywords: Product Quality, Brand Trust, Repurchase Intention, Customer Satisfaction